Odpowiedzi

2010-02-19T19:38:33+01:00
0,2*(-4)-0,2*(-8) = (-0,8)+1,6=0,8
(-6)*0,28-0,24*(-6)=(-1,68)+1,44=(-0,24)
4*(-1/3)-(-1/3)*(-5,6)= (-1⅓)-1 i 26/30 = 2,2
(-5/8)*1,4-1/4*1,4=(-0,875)-0,35=(-1,225)
3/4*(-0,6)-0,6*0,25=(-0,45)-0,15=(-0,6)
(-1,2)*1/3-(-2/3)*0,6=(-0,4)+0,4=0
Najlepsza Odpowiedź!
2010-02-19T19:56:24+01:00
0,2*(-4)-0,2*(-8)=-0,8-(-1,6)=-0,8+1,6=0,8
(-6)*0,28-0,24*(-6)=-1,68-(-1,44)=-1,68+1,44=-0,24
4*(-1/3)-(-1/3)*(-5,6)=(-1⅓)-1 i 26/30 = 2,2
(-5/8)*1,4-1/4*1,4=(-5/8)*7/5-1/4*7/5=-35/40-7/20=-35/40-14/40=-49/40
3/4*(-0,6)-0,6*0,25=3/4*(-3/5)-3/5*1/4=-9/20-3/20=-12/20
(-1,2)*1/3-(-2/3)*0,6=(-6/5)*1/3-(-2/3)*3/5=-6/15+6/15=0